Early structure formation in quintessence models and its implications for cosmic reionisation from first stars - Maio, Umberto; Meneghetti, Massimo; Bartelmann, Matthias (Arxiv, 2016)
We present the first hydrodynamic N-body simulations of primordial gas clouds responsible for the reionisation process in dark energy cosmologies. We compare the cosmological constant scenario with a SUGRA quintessence model with marked dynamics in order to highlight effects due to the different acceleration histories imposed by the dark energy. We show that both the number density of gas clouds and their clumpiness keep a record of the expansion rate during evolution, similar to the non-linear dark matter profile at virialisation, as was recently demonstrated by Dolag et al. (2004). Varying the shape of the primordial power spectrum, we show how this effect is mitigated by a running spectral index decreasing the power at small scales. Our results demonstrate that, in order to constrain the dark energy from large scale structures, one must track its effects down to the distribution of luminous matter.
Gesehen am 25.09.2017